The sea wolf - London, Jack 1876-1916 (Bantam Books, 1981)
Taken from the author's novel about Wolf Larsen and the thirty-foot sloop Spray in a story of man and his efforts to survive in the cold and inhospitable Arctic regions. The author illustrates social and biological theories exemplified in a life situation.